A randomized controlled trial to evaluate the benefits of a multimedia educational program for first-time hearing aid users - Ferguson, Melanie A.; Brandreth, Marian; Brassington, William; Leighton, Paul; Wharrad, Heather (Lippincott, Williams & Wilkins, 2016)
Objectives: The aims of this study were to (1) develop a series of short interactive videos (or reusable learning objects [RLOs]) covering a broad range of practical and psychosocial issues relevant to the auditory rehabilitation for first-time hearing aid users; (2) establish the accessibility, take-up, acceptability and adherence of the RLOs; and (3) assess the benefits and cost-effectiveness of the RLOs. Design: The study was a single-center, prospective, randomized controlled trial with two arms. The intervention group (RLO+, n = 103) received the RLOs plus standard clinical service including hearing aid(s) and counseling, and the waitlist control group (RLO−, n = 100) received standard clinical service only. The effectiveness of the RLOs was assessed 6-weeks posthearing aid fitting. Seven RLOs (total duration 1 hr) were developed using a participatory, community of practice approach involving hearing aid users and audiologists. RLOs included video clips, illustrations, animations, photos, sounds and testimonials, and all were subtitled. RLOs were delivered through DVD for TV (50.6%) and PC (15.2%), or via the internet (32.9%). Results: RLO take-up was 78%. Adherence overall was at least 67%, and 97% in those who attended the 6-week follow-up. Half the participants watched the RLOs two or more times, suggesting self-management of their hearing loss, hearing aids, and communication. The RLOs were rated as highly useful and the majority of participants agreed the RLOs were enjoyable, improved their confidence and were preferable to written information. Postfitting, there was no significant between-group difference in the primary outcome measure, overall hearing aid use. However, there was significantly greater hearing aid use in the RLO+ group for suboptimal users. Furthermore, the RLO+ group had significantly better knowledge of practical and psychosocial issues, and significantly better practical hearing aid skills than the RLO− group. Conclusions: The RLOs were shown to be beneficial to first-time hearing aid users across a range of quantitative and qualitative measures. This study provides evidence to suggest that the RLOs may provide valuable learning and educational support for first-time hearing aid users and could be used to supplement clinical rehabilitation practice.